Energy Performance of Buildings with Thermochromic Windows in Mediterranean Climates - Georgios E. Arnaoutakis (MDPI AG, 2021)
This article presents comparative results on the energy performance of buildings in the Mediterranean. Many buildings in the Mediterranean exhibit low energy performance ranking. Thermochromic windows are able to improve the energy consumption by controlling the gains from sunlight. In this article, reference buildings in 15 cities around the Mediterranean are investigated. In this work, a dynamic building information modeling approach is utilized, relying on three-dimensional geometry of office buildings. Calculations of the energy demand based on computational simulations of each location were performed, for the estimation of heating and cooling loads. The presented study highlighted the need for high-resolution data for detailed simulation of thermochromic windows in buildings of Mediterranean cities. Temperature is one of the main climate parameters that affect the energy demand of buildings. However, the climate of Mediterranean cities nearby the sea may affect the energy demand. This was more pronounced in cities with arid Mediterranean climate with increased demand in air-conditioning during the summer months. On the other hand, cities with semi-arid Mediterranean climate exhibited relatively increased heating demand. With this parametric approach, the article indicates the energy saving potential of the proposed measures for each Mediterranean city. Finally, these measures can be complemented by overall building passive and active systems for higher energy reductions and increased comfort.